Myosin heavy-chain isoforms in the flight and leg muscles of hummingbirds and zebra finches - Velten, Brandy P. (American Physiological Society, 2014)
Myosin heavy chain (MHC) isoform complement is intimately related to a muscle's contractile properties, yet relatively little is known about avian MHC isoforms or how they may vary with fiber type and/or the contractile properties of a muscle. The rapid shortening of muscles necessary to power flight at the high wingbeat frequencies of ruby-throated hummingbirds and zebra finches (25–60 Hz), along with the varied morphology and use of the hummingbird hindlimb, provides a unique opportunity to understand how contractile and morphological properties of avian muscle may be reflected in MHC expression. Isoforms of the hummingbird and zebra finch flight and hindlimb muscles were electrophoretically separated and compared with those of other avian species representing different contractile properties and fiber types. The flight muscles of the study species operate at drastically different contraction rates and are composed of different histochemically defined fiber types, yet each exhibited the same, single MHC isoform corresponding to the chicken adult fast isoform. Thus, despite quantitative differences in the contractile demands of flight muscles across species, this isoform appears necessary for meeting the performance demands of avian powered flight. Variation in flight muscle contractile performance across species may be due to differences in the structural composition of this conserved isoform and/or variation within other mechanically linked proteins. The leg muscles were more varied in their MHC isoform composition across both muscles and species. The disparity in hindlimb MHC expression between hummingbirds and the other species highlights previously observed differences in fiber type composition and thrust production during take-off.